Estudo de métodos de decapitação de citros, após a enxertia - Manica, Ivo; Andersen , Otto (Revista Ceres, 2025)
The present study was conducted in order to compare fivemethods ofdecapitation in citrus following budding. Rangpur lime was used as rootstock and ’Valencia’ orange as scion. Removal of the stock 2, 5 or 10 centimeters above the bud and partial cutting and bending the top of the stock away from the bud were equivalent in terms of percent survival and rate of growth, Looping the stock above the bud union without partial cutting resulted in a highly significant reduction in percent survival and rate of growth. Only 10% of plants treated in this manner acheived a height of 100 centimeters after 298 days. Growth curves were similar in all treatments except for the case in which the top of the stock was looped without parcial c utting. This treatment resulted in a marked reduction in growth during the later stages of the experiment. Rate of growth was twice as rapid the rainy season as compared with the dry season.